Acetylcholinesterase from Human Erythrocytes as a Surrogate Biomarker of Lead Induced Neurotoxicity. (22nd October 2015) - Gupta, Vivek Kumar; Pal, Rajnish; Siddiqi, Nikhat Jamal; Sharma, Bechan
Abstract : Lead induced neurotoxicity in the people engaged in different occupations has received wide attention but very little studies have been carried out to monitor occupational neurotoxicity directly due to lead exposure using biochemical methods. In the present paper an endeavour has been made in order to assess the lead mediated neurotoxicity by in vitro assay of the activity of acetylcholinesterase (AChE) from human erythrocytes in presence of different concentrations of lead. The results suggested that the activity of this enzyme was localized in membrane bound fraction and it was found to be highly stable up to 30 days when stored at −20°C in phosphate buffer (50 mM, pH 7.4) containing 0.2% Triton X-100. The erythrocyte's AChE exhibitedK m for acetylcholinesterase to be 0.1 mM. Lead caused sharp inhibition of the enzyme and its IC50 value was computed to be 1.34 mM. The inhibition of the enzyme by lead was found to be of uncompetitive type (K i value, 3.6 mM) which negatively influenced both theV max and the enzyme-substrate binding affinity. Taken together, these results indicate that AChE from human erythrocytes could be exploited as a surrogate biomarker of lead induced neurotoxicity particularly in the people occupationally exposed to lead.